Host perspectives on short-term experiences in global health: a survey. (April 2017) - Cherniak, William; Latham, Emily; Astle, Barbara; Anguyo, Geoffrey; Beaunoir, Tessa; Buenaventura, Joel H; DeCamp, Matthew; Diaz, Karla; Eichbaum, Quentin; Hedimbi, Marius; Myser, Cat; Nwobu, Charles; et al.
Abstract: Background: Competencies developed for global health education programmes that take place in low-income and middle-income countries have largely reflected the perspectives of educators and organisations in high-income countries. Consequently, there has been under-representation of voices and perspectives of host communities, where practical, experience-based global-health education occurs. In this study, we aimed to understand what global-health competencies are important in trainees who travel to work in other countries, seeking opinions from host community members and colleagues in low-income and middle-income countries. Methods: We performed a literature review of current interprofessional global health competencies to inform our survey design. We used a web-based survey, available in English and Spanish, to collect data through Likert-scale and written questions. We piloted the survey in a diverse group of 14 respondents from high-income, middle-income, and low-income countries and subsequently refined the survey for greater clarity. We used convenience sampling to recruit participants from around the world and included a broad range of coauthors. A website was constructed in English and Spanish and the survey link added. This website and link were distributed as broadly as possible. It was mandatory for survey participants to list their country of birth and current work in order to confirm representation. Findings: We received 274 responses: 227 in English and 47 in Spanish between Sept 1, 2015, and Dec 31, 2015. Respondents were from 38 countries across all economic regions. After data cleaning, we included 170 responses (132 in English and 38 in Spanish): 44 (26%) from high-income countries, 74 (44%) from upper-middle income countries, 31 (18%) from lower-middle income countries, and 21 (12%) from low-income countries. Respondents spoke 22 distinct primary languages. In terms of pre-departure competencies, 111 respondents rated cultural awareness and respectful conduct while on rotations as important. For intra-experience competencies, 88 of 112 respondents (79%) thought that it was equally as important for trainees to learn about the local culture as it was to learn about medical conditions. 65 of 109 (60%) respondents reported trainees gaining fluency in the local language as being not important. In terms of post-experience competencies, none of the respondents reported that trainees arrive as independent practitioners to fill health-care gaps. Interpretation: Most hosts and partners across economic regions appreciate having trainees from other countries in their institutions and communities. There was a strong emphasis from respondents on the importance of a greater focus on cultural learning and building respect over medical knowledge and clinical practice. Additionally, respondents did not believe that trainees fill important human resource gaps, but are instead being provided with a beneficial learning experience. By gaining insight into host perceptions on desired competencies, global health education programmes in low-income and middle-income countries can be collaboratively and ethically designed and implemented to meet the priorities, needs, and expectations of host communities. Our findings could change how global health education programmes are structured, by encouraging North-South/East-West shared agenda setting, mutual respect, empowerment, and collaboration. Funding: Child Family Health International.